2023
DOI: 10.24018/ejbmr.2023.8.1.1797
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Workload, Perceived Organizational Support, and Time Management on Academic Procrastination with Work School Conflict as a Mediating Variable

Abstract: Every company needs to improve the performance of their employees to achieve company goals, especially for the current era of globalization. One of the things that can improve employee performance is continuing education. An increase in the number of Master of Management Students who decide not to be active and take time off from lectures at MB University is an interesting phenomenon to study. The purpose of this study is to determine the effect of workload, perceived organizational support, and time managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…So it can be concluded that time management has a positive and significant effect on the perceptions of student members of the Universitas Mikroskil student organization This finding is also relevant to several similar studies which emphasize the importance of time and this part is the novelty of this research, like one finding have shown that the incorporation of a time management enabling assist students in practising time management (Khiat, 2022). And the other finding that state students should continue to maintain in managing the balance between work and lectures so that they are able to carry out these two activities simultaneously by preparing activity plans and re-examining these plans (Sulistia and Widigdo, 2023) and by all these reasons we clarify that time management on behavior and perception in organizational skills as important soft skills for students specially for students organizations.…”
Section: The Effect Of Time Management On the Behavior Of Student Mem...mentioning
confidence: 52%
“…So it can be concluded that time management has a positive and significant effect on the perceptions of student members of the Universitas Mikroskil student organization This finding is also relevant to several similar studies which emphasize the importance of time and this part is the novelty of this research, like one finding have shown that the incorporation of a time management enabling assist students in practising time management (Khiat, 2022). And the other finding that state students should continue to maintain in managing the balance between work and lectures so that they are able to carry out these two activities simultaneously by preparing activity plans and re-examining these plans (Sulistia and Widigdo, 2023) and by all these reasons we clarify that time management on behavior and perception in organizational skills as important soft skills for students specially for students organizations.…”
Section: The Effect Of Time Management On the Behavior Of Student Mem...mentioning
confidence: 52%